2019
DOI: 10.1093/ej/uez002
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Growth in a Technologically Progressive Economy: The United States, 1899–1941

Abstract: We develop new aggregate total factor productivity (TFP) growth estimates for the USA between 1899 and 1941, and sectoral estimates at the most disaggregated level so far, 38 industries. We include hard-to-measure services, and a refined measure of sectoral labour quality growth. The resulting data set supersedes Kendrick (1961), showing TFP growth lower than previously thought, broadly based across industries, and strongly variant intertemporally. The four ‘great inventions’ that Gordon (2016) highlighted wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Historical analysis has focussed on productivity trends in previous technology phases (Bakker et al, 2019;Crafts, 2004). Recent literature has shown that the information and communication technology (ICT) revolution of the past 50 years can be characterised as a GPT and doesn't pale with previous GPTs such as steam technology, electricity and the combustion engine.…”
Section: The Productivity Paradox Of the New Digital Economymentioning
confidence: 99%
“…Historical analysis has focussed on productivity trends in previous technology phases (Bakker et al, 2019;Crafts, 2004). Recent literature has shown that the information and communication technology (ICT) revolution of the past 50 years can be characterised as a GPT and doesn't pale with previous GPTs such as steam technology, electricity and the combustion engine.…”
Section: The Productivity Paradox Of the New Digital Economymentioning
confidence: 99%
“…Field (2003) andAlexopoulos and Cohen (2009) argue that the 1930s were the single most innovative U.S. decade of the 20 th century Gordon (2016). andBakker et al (2019) provide (different) updated time series estimates of U.S. TFP growth to argue that, while the 1930s were an innovative period (with faster TFP growth than the decades preceding it), it was less innovative than the decades that followed (during and immediately after World War II).18 In standard neoclassical growth models, a permanent change in the level of employment would not affect steadystate capital per worker. Of course, changes in risk premia or other factors affecting the relative cost of capital to labor would affect capital per worker.…”
mentioning
confidence: 99%
“…It is also true that a comparison with the United States in the interwar period also looks a bit better partly because new research has revised downwards American TFP growth by taking fuller account of labour quality than was done by Kendrick (1961). Whereas comparing Matthews et al for 1924to 1937with Kendrick for 1919to 1941 showed UK TFP growth at 0.2 per cent versus US TFP growth at 2.16 per cent per year, the new estimates are 0.41 per cent for the UK compared with 1.76 per cent per year for the United States according to Bakker et al (2019). That said, UK productivity growth is still a long way below the American level and this remains a big caveat on optimistic interpretations of interwar British performance.…”
Section: Discussionmentioning
confidence: 92%